Groups Proper Nonmaximal Subgroups of Which Are Cyclic or Minimal Noncyclic - Koval, Т. V. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We constructively describe locally graded groups all proper nonmaximal subgroups of which are cyclic or minimal noncyclic.